Applicability of low-temperature thermochronology to the evolution of young (< ~ 5 Ma) orogenic systems: a case study from the Japanese Islands - Shigeru Sueoka; Takahiro Tagami (Progress in Earth and Planetary Science)
Abstract Low-temperature thermochronology, including fission track (FT) and (U–Th–Sm)/He thermochronometry, has been widely used to constrain the exhumation history of orogenic systems over timescales of 106–108 years. This research employed simple numerical modeling to evaluate the applicability of low-temperature thermochronometry to young orogenic systems uplifted in geologically recent periods such as the Pliocene and Quaternary, such as those in the Japanese Islands. Such orogenic systems are at the younger limit of the applicability because this time scale corresponds to the younger limit of applicability of the major low-temperature thermochronometers and also corresponds to the minimum period required for an orogenic system to be denuded by more than ~ 2–3 km after the start of uplift, which is the lower limit detectable by the major low-temperature thermochronometers. Time‒temperature paths were generated for varying uplift rates, uplift onsets, and model onsets (equivalent to the rock formation age). These paths were then converted into cooling ages for four thermochronometers: apatite and zircon FT and (U–Th–Sm)/He dating. The calculations were conducted using two models: a constant-elevation model and an increasing-elevation model. The modeling results are summarized in look-up tables, illustrating relationships between uplift rates, uplift onsets, rock formation ages and ratios of cooling age and rock formation age. The results indicate that differences in formation age and elevation change minimally impact cooling ages. The modeled dates generally align with measured cooling ages in regions where the rate and timing of uplift are well constrained, supporting the reliability of the modeling approach. Consequently, the derived relationships between uplift rates and cooling ages provide a practical method for roughly classifying mountain uplift rates based on cooling ages, without requiring complex simulations. Finally, these relationships were applied to previously reported cooling ages to visualize the distribution of uplift rates across the Japanese Islands over the past few million years. These results provide a benchmark for the low-temperature thermochronological studies, not only in the Japanese Islands, but also in mobile belts around the world that have begun to uplift in the past few million years.